2016
DOI: 10.1007/s10725-016-0149-z
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroids increase winter survival of winter rye (Secale cereale L.) by affecting photosynthetic capacity and carbohydrate metabolism during the cold acclimation process

Abstract: The aim of the study was to verify the hypothesis that brassinosteroids would modify the cold acclimation process through the stimulation of photosynthesis and carbohydrate metabolism, and would consequently cause an increase in the plant's capacity for winter survival. Seedlings of two winter rye cultivars (winter-resistant and moderately winter-resistant types) were sprayed with 24-epibrassinolide (EBR) and then subjected to cold acclimation at 4°C. The foliar hormone application was studied for its effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…ABA abscisic acid, SA salicylic acid, HCS homocastasterone, CS castasterone, TE teasterone, DL dolicholide, Sc control seedlings/heading plants sensitive to freezing/drought treatment, Tc control seedlings/heading plants tolerant to freezing/drought treatment, S H cold hardened seedlings sensitive to freezing stress, T H cold hardened seedlings tolerant to freezing stress, S D drought treated plants sensitive to drought stress, T D drought treated plants tolerant to drought stress 1 3 freezing tolerance, whereas disturbances in later stages of BR biosynthesis had no effect. According to literature, the content of BRs increased in cold hardened winter rye (Pociecha et al 2016) and spring barley (Sadura et al 2019), which is to some extent in accordance with data obtained in this study as significant increase in HCS content was noted for more freezing tolerant DH lines of barley. Previous studies with spring barley (Sadura et al 2019) and winter wheat (Janeczko et al 2019) also showed that cultivars less tolerant to freezing accumulated lower amounts of BRs (especially HCS) in response to cold hardening in comparison with more tolerant cultivars.…”
Section: Changes In Phytohormone Content Associated With Stress Treatsupporting
confidence: 92%
“…ABA abscisic acid, SA salicylic acid, HCS homocastasterone, CS castasterone, TE teasterone, DL dolicholide, Sc control seedlings/heading plants sensitive to freezing/drought treatment, Tc control seedlings/heading plants tolerant to freezing/drought treatment, S H cold hardened seedlings sensitive to freezing stress, T H cold hardened seedlings tolerant to freezing stress, S D drought treated plants sensitive to drought stress, T D drought treated plants tolerant to drought stress 1 3 freezing tolerance, whereas disturbances in later stages of BR biosynthesis had no effect. According to literature, the content of BRs increased in cold hardened winter rye (Pociecha et al 2016) and spring barley (Sadura et al 2019), which is to some extent in accordance with data obtained in this study as significant increase in HCS content was noted for more freezing tolerant DH lines of barley. Previous studies with spring barley (Sadura et al 2019) and winter wheat (Janeczko et al 2019) also showed that cultivars less tolerant to freezing accumulated lower amounts of BRs (especially HCS) in response to cold hardening in comparison with more tolerant cultivars.…”
Section: Changes In Phytohormone Content Associated With Stress Treatsupporting
confidence: 92%
“…This phenomenon did not occur during recovery under irradiance of 100 μmol m -2 s -1 . An increase in Rubisco activity after 24-epibrassinolide application was also confirmed by Pociecha et al (2016) in a study on winter rye plants exposed to 3 and 6 weeks of cold. On the other hand, in perennial ryegrass, when 24-epibrassinolide (0.25 mg dm -3 ) was applied before plant exposure to 4 ºC for 6 weeks, the Rubisco activity was reduced by about 30 % but only in sensitive cv.…”
Section: Gas Exchange Photosystem Activities and Co 2 Assimilationmentioning
confidence: 53%
“…in plants grown at 26 °C. In turn, Pociecha et al (2016) showed that the castasterone content in rye grown at 18 °C is 4 -5 pmol g -1 (f.m. ), however, as a result of six weeks of cold, this content increases to about 14 -16 pmol g -1 (f.m.).…”
Section: Mobilization Of Cellular Antioxidant Systemmentioning
confidence: 98%
See 1 more Smart Citation
“…After this period, the plant survival rate was estimated based on the Larsen (1978) visual scale (0-9 scale of regrowth after frost treatment), where 0 indicates completely dead plants with no signs of leaf elongation, whereas 9 means no symptoms of injury. For a detailed description of the scale see Pociecha et al (2016).…”
Section: Frost Test and Estimation Of The Plant Survival Ratementioning
confidence: 99%